PROFIL WANITA PEKERJA DI PABRIK SARDEN PT. MAYA DESA KEDUNGREJO KECAMATAN MUNCAR KABUPATEN BANYUWANGI - Aginta Nortadhoh; Sri Wahyuni; Bambang Suyadi (Economic Education, University of Jember, 2017)
The purpose of this study is to find characteristic of a woman workers , picture in a public sector and sector domestic, marginalisasi, and allocation of time working woman. Characteristic of a woman workers in this research seen from age working woman, status marriage, the number of dependents children, and length of employment which will would bring them to different characters with the woman not worked so as bring up motiv its own for women workers. To know picture working woman in a public sector and sector domestic. Marginalisasi woman workers at a factory sardines Maya Kedungrejo Muncar Banyuwangi intended here differences in placement a position between working man with working woman. Allocation of time intended here to see how working woman set time to work in a factory, doing his job as a housewife, and when they with the community about his house. The kind of research this is the qualitative study. Research locations determined by means of purposive the area that carried out in in a factory sardines PT. Maya Kedungrejo Muncar Banyuwangi. Data were collected by using the method observation, interview, the literature study, and documentation. Informants in this research was workers woman who works in a mill PT. Maya Kedungrejo Muncar. Data analysis used , namely analysis research descriptive qualitative. The research results show that characteristic of a woman workers in a factory Maya Kedungrejo Muncar are women those who has married, with families to, the husband is work and become the backbone of family, and women who still carrying out their obligations as a housewife namely the house, husband, and their children. Woman working on public sector tends to be dominant than domestic for the sectors. Woman workers at a factory sardines maya there are still many work in position production so marginalisasi on workers women still very looked. In the allocation of their time affecting income that they can.